AN ANALYSIS OF STUDENTS’ WRITING SKILL THROUGH FACEBOOK AS A MEDIA - Aulia Hanifah Qomar (Universitas Ahmad Dahlan)
The aim of this study were 1) to analyze the students’ writing ability using facebook as a media, and 2) to know the classroom situations when Facebook as a media implemented in the writing class. This study is qualitative study which is carried out at Muhammadiyah University of Metro. In collecting the data, the researcher used test, observation and interview. The research findings showed that Facebook as a Media can improve the students’ writing skill. Those improvements were: 1) the students’ used effective word or diction choice and usage word from mastery, appropriate register; 2) the students were fluent expressions, ideas clearly stated/support, and well organized. Then, related to the classroom situation, the researcher found that: 1) teaching and learning process was more effective; 2) the students did the task given by the lecturer; 3) the students needed long time in using facebook; 4) time management was not control (internet connection).